The Human Rights Situation in Iraq from 1991 to 2003 in the Reports of the United Nations Commission on Human Rights - Jalel hama Huseen Salah (Journal of College of Education, 2025)
This research paper examines the state of human rights in Iraq during the period from 1991 to 2003, based on reports issued by the United Nations Commission on Human Rights. It highlights the international attention given to the human rights situation in Iraq during that time, particularly following the Gulf War. The study also reviews the efforts and activities undertaken by the United Nations through its special committees to investigate and document human rights violations. Furthermore, it discusses the deterioration of human rights conditions during those years, as well as the political, social, and economic factors that contributed to this situation. Finally, the paper points to the changes and reforms that emerged after the war, aimed at promoting individual freedoms and safeguarding citizens’ rights.
Keywords: united nations; human rights; Max van der StoelK; Andreas Mavromatis; Iraq